Implementasi pendidikan akidah akhlak dalam membentuk sikap sopan santun siswa SMK Muhammadiyah 4 Surakarta Tahun Pelajaran 2022/2023 - Hanifah Nur; Isfihani; Praptiningsih (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims to find out how far the implementation of aqidah moral education is in shaping the politeness of students at Muhammadiyah 4 Surakarta Vocational School in the 2022/2023 academic year. This type of research is research that uses qualitative methods, namely through the observation stage which aims to observe student attitudes, interviews to obtain research-related information from informants, documentation to obtain data or documents related to student morals. The results of this study indicate that the implementation of aqidah moral education at SMK Muhammadiyah 4 Surakarta is quite effective, the proof is that most of the students are able to apply aqeedah moral education in being polite well, through refraction and practicing morals in everyday life, and in this study also shows the supporting factors and inhibiting factors in the implementation of aqidah moral education in shaping students' polite attitudes.